Research progress on the diagnostic techniques and vaccine development of bovine herpesvirus types 1 - Zhang, Jianming; Cao, Jian; Cao, Liang; Zhang, Chao; Gong, Liyuan; Kang, Xiaohong; Li, Dehong; Zhang, Yang (Frontiers in Veterinary Science, 2025)
Bovine herpesvirus type 1 (BoHV-1) constitutes a major etiological agent associated with the onset of bovine respiratory disease in cattle. This virus is widely prevalent across global cattle populations, leading to significant economic losses. The advancement of early diagnostic methodologies and the formulation of effective vaccines are crucial for the prevention, control, and potential eradication of BoHV-1. This review offers a comprehensive overview of current diagnostic methodologies for BoHV-1, encompassing serological diagnostic approaches, molecular detection methods, and emerging novel techniques. Furthermore, recent development in vaccine research targeting BoHV-1 infection are discussed. Ultimately, this review aims to provide critical insights into the management of BoHV-1 infection, and guide future research efforts in the enhancement of diagnostic tools and vaccine strategies.